Cardiovascular Diseases and Schizophrenia in India: Evidence, Gaps, and Way Forward - Padmavati, Ramachandran; Kantipudi, Suvarna Jyothi; Balasubramanian, Suhavana; Raghavan, Vijaya (Frontiers in Psychiatry, 2021)
Background: There is an increase in the recognition of the importance of physical health among patients with mental disorders in the past few years, especially among patients with serious mental disorders. Though literature has shown strong association between cardiovascular diseases and serious mental disorders, evidence from India is scattered and still in its infancy. Hence, the aims of the study were to collate available studies from India on cardiovascular diseases among patients with serious mental disorders, identify knowledge gaps and challenges and discuss recommendations to improve clinical care and research on cardiovascular diseases among patients with serious mental disorders. Materials and methods: A comprehensive literature review of Indian studies on cardiovascular diseases and serious mental disorders were conducted to collate and synthesize available knowledge. To complement this, secondary data analysis was done on existing datasets from two large tertiary heath care institutions from Chennai, India on cardiovascular diseases among patients with serious mental disorders. Results: Results from the comprehensive review of literature and secondary data analysis indicate a high prevalence of risk factors for cardiovascular disease among patients with serious mental disorders. Knowledge gaps were identified with respect to the prevalence of cardiovascular diseases among patients with serious mental disorders, holistic approach towards studying the risk factors for cardiovascular diseases among patients with serious mental disorders and interventions to prevent and reduce the impact of cardiovascular diseases among patients with serious mental disorders. Conclusion: Targeted efforts are needed at the clinic, community and policy level to understand the impact of cardiovascular diseases among patients with serious mental disorders and development and testing of robust and feasible interventions targeting cardiovascular diseases and its varied risk factors in patients with serious mental disorders.